Feature engineering combined with machine learning and rule-based methods for structured information - Chang, Eric (Journal of the American Medical Informatics Association, 2012)
A system that translates narrative text in the medical domain into structured representation is in great demand. The system performs three sub-tasks: concept extraction, assertion classiﬁcation, and relation identiﬁcation.